The Effect Of Work Ethic, Communication And Teamwork On Employee Performance In Job Satisfaction Mediation At Bank Indonesia Representative Office In North Sumatra Province - Muhammad Imam; Mesra B (Yayasan Multidimensi Kreatif, 2024)
Human beings need special attention because they are basically able to develop, have intellect, ideas, feelings, desires, and hopes. These variables also affect achievement, dedication, loyalty, and love for work and the success of the organization. The results of this study are as follows: Work ethic has a positive and significant effect on Job Satisfaction with the original sample value of 0.356 and p values of 0.005. Work Ethic had a positive and insignificant effect on Employee Performance with the original sample value of 0.138 and p values of 0.056. Job Satisfaction had a psoitative and significant effect on Employee Performance with the original sample value of 0.133 and p values of 0.003. Teamwork had a positive and insignificant effect on Job Satisfaction with the original sample value of 0.217 and p values of 0.062. Teamwork had a positive and insignificant effect on Employee Performance with the original sample value of 0.020 and p values of 0.363. Communication had a positive and significant effect on Job Satisfaction with the original sample value of 0.382 and p values of 0.000. Communication had a positive and significant effect on Employee Performance with the original sample value of 0.719 and p values of 0.000. Work Ethic has a positive and significant effect on Employee Performance through Job Satisfaction with a value of 0.047 and p values of 0.031 Communication has a positive and significant effect on Employee Performance with an original sample value of 0.051 and p values of 0.028. Work Ethic has a positive and significant effect on Employee Performance through Job Satisfaction with a value of 0.047 and p values of 0.031. Communication has a positive and significant effect on Employee Performance with original sample values of 0.051 and p values of 0.028